Sleep Habits in Students with Intellectual Disability - Zahra Mortazavi; Hojjat allah Haghgoo; Nasrin Gohari; Kimia Bakhtiari; Salman Khazaei; Saideh Sadat Mortazavi (Journal of Sleep Sciences, 2022)
Background and Objective: Sleep habits not only are affected by a person’s health but also affect his/her growth and development. Students with intellectual disability (ID) account for 3% of all students. Since sleep habits are among the basic foundations of learning during childhood, this study aimed to determine the parental view on the sleep habits of students with ID in Hamadan, Iran, during September 23 and December 21, 2019.